2022
DOI: 10.1038/s41586-021-04238-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergent interface vibrational structure of oxide superlattices

Abstract: As the length scales of materials decrease, the heterogeneities associated with interfaces become almost as important as the surrounding materials. This has led to extensive studies of emergent electronic and magnetic interface properties in superlattices1–9. However, the interfacial vibrations that affect the phonon-mediated properties, such as thermal conductivity10,11, are measured using macroscopic techniques that lack spatial resolution. Although it is accepted that intrinsic phonons change near boundarie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 63 publications
0
47
0
Order By: Relevance
“…As further validation, we conducted off-axis EELS measurements from the epi-SLs and isolated QDs. By collecting EELS many tens of milliradians away from the optic axis of the electron microscope, the contribution from the delocalized dipole scattering is minimized, facilitating the identification of highly-localized emergent properties 37 . The measurements shown above were performed on-axis to maximize the signal to noise, but Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As further validation, we conducted off-axis EELS measurements from the epi-SLs and isolated QDs. By collecting EELS many tens of milliradians away from the optic axis of the electron microscope, the contribution from the delocalized dipole scattering is minimized, facilitating the identification of highly-localized emergent properties 37 . The measurements shown above were performed on-axis to maximize the signal to noise, but Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The acoustic branch shows high dispersion when compared to the optical branch at the interface across the Brillouin zone (Γ−Σ−K−X), resulting in thermal transport across the interface. In parallel, other researchers measured the phonon modes in strontium titanate−calcium titanate superlattices 50 and silicon−germanium interfaces 51 to map the spatial extent of interfacial phonon modes. Recent work by Gadre et al 52 observed that abrupt Si−Ge interfaces impede the phonon propagation to a higher degree than gradual interfaces, thus explaining the decrease in the thermal conductivity at abrupt interfaces.…”
Section: Momentum-resolved Vibrational Eels (Q-eels)mentioning
confidence: 99%
“…It has helped tie together the structure-property relationships in materials systems as diverse as interfaces [12], superlattices [13], domain walls [14,15], grain boundaries [16], nanoparticles [17], and catalyst surfaces [18]. This has led to the discovery of novel applications such as phonon modes at polar vortices and two-dimensional electrical liquids at oxide interfaces [19][20][21]. In the physical sciences, these applications have been in fields as diverse as lithium-ion batteries, catalyst systems, and alloy designs to integrate electronic circuits [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%